Capacity Building of Rural Women in Dairy Farming : An Impact Assessment - Akila N; Senthilvel K (Indian Journal of Extension Education, 2013)
The study on adoption of dairy farming technologies by rural women in Karur district of Tamil Nadu revealed that the rural women were involved in all activities to take care of the animals except decision regarding marketing milk, purchase and sale of animals. Green fodder production (24%), pregnant animal care (21%), importance of deworming (19%), maintaining dry period (9%), and clean milk production (5%) were the technologies least adopted by the respondents before training. After the training, considerable improvement was seen among the trainees in adopting the technologies like deworming (96%), artificial insemination (98%), vaccination and mineral mixture feeding (97%). Lack of remunerative price for milk is the major constraint faced by the respondents followed by high cost of feed.